Run-off modeling and mapping using rainfall and evapotranspiration estimates from remote sensing satellite data in Peninsular Malaysia - Mohd. Rizaludin Mahmud, 1985-; Mazlan Hashim, supervisor; Fakulti Geoinformasi dan Harta Tanah (2011)
Thesis (Sarjana Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2011